2015
DOI: 10.1074/jbc.m115.669929
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Complex of Neurodegeneration-related Phosphoinositide Phosphatase Sac3 and ArPIKfyve Binds the Lewy Body-associated Synphilin-1, Preventing Its Aggregation

Abstract: Background:The cytosolic ArPIKfyve-Sac3 complex binds PIKfyve to regulate housekeeping endosomal functions but other tissue-specific interactors and functions are unknown. Results: Brain Synphilin-1 is a novel interaction partner of the ArPIKfyve-Sac3 complex. Conclusion:The ArPIKfyve-Sac3 complex is an effective inhibitor of aggregate formation by Synphilin-1. Significance: The novel molecular means for reducing cytoplasmic aggregates of Synphilin-1 provides new insights into neurodegeneration mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…Indeed, our mass spectrometry experiments (in Figure 4) revealed several phosphorylated sites on PIKfyve unattributable to its auto-kinase activity. Additionally, Vac14 has been reported to interact with a host of proteins, including Rabs, RabGEFs, RabGAPs, BAR domain proteins, scaffolding proteins, and others (Currinn et al, 2016;Ikonomov et al, 2015;Jin et 2016;Malia et al, 2018;Mayer et al, 2018;Schulze et al, 2014), which could modulate and be modulated by its interaction with the membrane and with PIKfyve and Fig4. These interactions likely play a role in spatiotemporal regulation of PIKfyve and Fig4 enzymatic activities, as well as signaling between the PIKfyve complex and regulators and effectors.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…Indeed, our mass spectrometry experiments (in Figure 4) revealed several phosphorylated sites on PIKfyve unattributable to its auto-kinase activity. Additionally, Vac14 has been reported to interact with a host of proteins, including Rabs, RabGEFs, RabGAPs, BAR domain proteins, scaffolding proteins, and others (Currinn et al, 2016;Ikonomov et al, 2015;Jin et 2016;Malia et al, 2018;Mayer et al, 2018;Schulze et al, 2014), which could modulate and be modulated by its interaction with the membrane and with PIKfyve and Fig4. These interactions likely play a role in spatiotemporal regulation of PIKfyve and Fig4 enzymatic activities, as well as signaling between the PIKfyve complex and regulators and effectors.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…In addition, Fig4 is involved in both the biosynthesis and turnover of PtdIns(3,5)P 2 ( 4 , 61 , 62 ), which likely requires more delicate control of expression levels. Along the same line, it was reported that overexpression of Fig4 potentiated the aggregation of Lewy body–associated Synphilin-1 protein, while overexpression of Vac14 alleviated the aggregation ( 34 ).…”
Section: Discussionmentioning
confidence: 67%
“…Surface levels of AMPA-type glutamate receptors are increased in Vac14 −/− and Fig4 −/− neurons due to altered internalization and recycling to the plasma membrane. In addition, Vac14 physically interacts with amyloid precursor protein (APP) ( 32 , 33 ), the central player in Alzheimer's disease, and synphilin-1, an aggregation-prone protein implicated in Parkinson's disease ( 34 ). Inhibition of PtdIns(3,5)P 2 pathway results in the accumulation of APP in early endosomes ( 33 ).…”
mentioning
confidence: 99%
“…Одним из продуктов разрушения нейронов является α-синуклеин -сложный структурный белок нервных клеток, оказывающий прямое стимулирующее действие на толлподобные рецепторы [14]. Их активация приводит к стимуляции активности тканевых макрофагов, входящих в состав микроглии [15], и выбросу провоспалительных цитокинов: ФНОα; ИЛ-1β, ИЛ-6 и ИЛ-15 [16]. Наличие в ткани головного мозга ФНОα и ИЛ-1β обеспечивает положительный хемотаксис лейкоцитов [17].…”
Section: результаты и обсужденияunclassified